Efeito do número de pinos de fibra de vidro na resistência à fratura, deformação estrutural e distribuição de tensão em molares tratados endodonticamente - Barcelos, Luciana Mendes (2016)
The aim of this study was to evaluate the biomechanical effect of the presence and number of fibreglass post in endodontically treated molars restored with composite resin. 45 human molars were selected, included in polystyrene resin cylinders with simulation of the periodontal ligament and endodontically treated. These teeth were randomized into three groups (n = 15): Wfgp, without fibreglass post and restored with Filtek Z350 XT; 1fgp, 1 fiberglass post Exact #2 cemented in the distal root with RelyX U200 and restored with Z350XT; and 2fgp, 2 fiberglass posts cemented with RelyX U200, one in the distal root and the other in the mesiobuccal root, restored with Z350XT. The specimens were submitted to mechanical fatigue with axial load of 50N. The tooth remaining deformation was measured using extensometers (n = 10) during occlusal loading of 100N and then until fracture. The other teeth (n = 5) were used to calculate the modulus of elasticity (GPa) and Vickers hardness (VH, N/mm2) of the enamel, dentin composite resin and fiberglass post in two positions: parallelly and transversally to the long axis of the post. The stress distribution was analyzed using three dimensional finite elements model, generated from micro-CT image of an intact tooth with its geometry similar of those used in the in vitro study. The calculated mechanical properties were used to characterize models of finite element analysis. The data of deformation and fracture resistance were tested for normality (Shapiro-Wilk) and equivalence of variances (test Levene), followed by parametric statistical tests appropriated for each test. One way Anova was performed for the axial compressive strength values, tooth remaining deformation and fracture resistance. Multiple comparisons were performed using Tukey test. The mean fracture data were submitted to the Chi-square test. Factorial analysis of variance on two factors was carried out considering as factors in study: the tooth surface deformation (B and L) and rehabilitation technique. All tests done had significance level α = 0.05 and all analyses were performed with the statistical program Sigma Plot version 13.1 (Systat Software, San Jose, CA, USA). The use of two fiber glass posts resulted in lower fracture resistance than the groups without fiber glass - 22 - post and with one fiber glass post. During occlusal loading of 100N lingual surface of the remaining tooth showed higher deformation for all groups. The absence of fiber glass post resulted in significantly higher values of stress in the root and more irreparable fracture modes than the other groups. The use of a fiber glass post resulted in better ratio deformation/fracture resistance. The concentration of stress in the furcation area was slightly reduced with use of fiber glass post. It is concluded that the use of one fiber glass post to rehabilitated molars with direct composite resin showed higher resistance to fracture than the use of two fiberglass posts, lower tooth remaining deformation, better stress distribution and failure pat more repairable when compared to molars restored without use of fiber-glass post